Kejiwaan Tokoh Utama dalam Novel Acha Goodbye karya Yesycha Mangopo (2021): The Psychological State of the Main Character in the Novel Acha Goodbye by Yesycha Mangopo (2021) - Komala, Dian; Musa, Safuri; Huri, Daman (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study focuses on the psychology of the main character in a literary work. The literary work that is the subject of this study is a novel. One novel that examines the psychology of the main character is Acha Goodbye by Yesycha Mangopo (2021). This study uses the theory of literary psychology, namely David Krech's Classification of Emotions (1974). The method used in this study is a descriptive qualitative approach, based on the results of an in-depth study of the novel Acha Goodbye by Yesycha Mangopo (2021). David Krech's Classification of Emotions (1974), as found in the novel Acha Goodbye by Yesycha Mangopo (2021), includes aspects of repressed guilt, shame, sadness, anger, and love experienced by the main character, Anasthacya Friska Breklin, who is known as Acha or by her childhood name, Cia. Acha's sadness, mixed with anger, stems from her being ostracized by her family. Her family ostracized Acha because she could not share a roof with Eca (Acha's twin) due to health problems. Even though Acha also had the same illness as Eca, her family ignored her. Her family always put Eca first. Therefore, the main character Acha in the novel Acha Goodbye by Yesycha Mangopo (2021) experienced psychological disturbances due to her family's treatment of her isolation. This provides evidence that Acha, the main character in a literary work, is a paradigm of human life in the real world. Arbitrary family treatment causes people's psychological health to experience mental health disorders.